VIDEO REPORT USING ANDROID APPLICATION FOR IMPROVING STUDENTS' INFORMATION LITERACY IN LEARNING SOLAR SYSTEM - Hurin Azka Millatina, - (2020)
This study aims to investigate the effect of making a video report in learning Solar System can improve the information literacy skill of 7th-grade students. This study was conducted in a private school in Bandung. This research is used weak experimental research used one group pre-test post-test design. A sample of 32 students was selected conveniently from one class available in the school. All of the samples are treated by making the video report in the moon phases model simple project. The data was collected via the pre-test and post-test administration and Questionnaire to strengthen the result of students' information literacy skills. The video report product also assesses by using the video report rubric. The results were statistically analyzed by using SPSS software by employing a paired sample t-test. The result shows 0.55 which is categorized into middle based on the category in Normalized Gain. Results indicate that after applied the treatment to the students, there is an improvement of students' Information Literacy skills after making the video report. Therefore, the result of students' information literacy showed that there was a significant difference between the result of the post-test and the result of the standard average of the knowledge dimension. It is concluded that making a video report is useful to conduct as the learning strategy to improve students' Information Literacy Skills.